ANALYSIS OF FACTORS RELATED TO EMOTIONAL DEVELOPMENT IN ELEMENTARY SCHOOL CHILDREN - Tyas, Anestasia Pangestu Mei; Putri Sherly, Pratama; Mardhika, Amellia; Fadliyah, Lailatul; Sulpat, Emuliana; Ilkafah, Ilkafah (Universitas Airlangga, 2025)
Introduction: Middle childhood is a crucial period for developing emotions, including recognizing, expressing, and regulating them. Several factors influence a child’s emotional development. This study aimed to analyze the factors related to emotional development in elementary school children. Methods: This study employed an observational analytical design with a cross-sectional approach. The sample consisted of 55 respondents selected using purposive sampling according to predetermined inclusion criteria. The independent variables were the child’s sex, gadget use, parents’ age, occupation, and education level. The dependent variable was emotional development. Data were collected using questionnaires assessing the child’s sex, parents’ age, education, and occupation, as well as the Pediatric Symptom Checklist–17 (Indonesian version) and a questionnaire on gadget use. Data were analyzed using the chi-square test and multiple logistic regression with the assistance of SPSS. Results: There was a significant relationship between gadget use and emotional development among children at school (p = 0.006), with an odds ratio of 5.365. This indicates that children who use gadgets are five times more likely to experience emotional problems than those who do not. Conclusions: It is necessary to establish parenting patterns for gadget use in the digital era, including setting clear rules and time limits, accompanying children during gadget use, selecting age-appropriate content, supervising online activities, and serving as role models for the wise use of gadgets to support the emotional development of school-aged children.